Love Them & Leave Them: science-based rationale for a campaign at the public health-conservation interface - Reaser, Jamie K.; Li, Hongying; Southey, Sean (Frontiers in Conservation Science, 2025)
Wild animals have been implicated as the source for disease outbreaks in humans (e.g., bubonic plague, Ebola, Hendra virus). Public health messaging intended to mitigate these zoonotic disease risks can inadvertently induce fear of wildlife, thereby resulting in wildlife culling and habitat destruction. We propose a science-based social marketing campaign – Love Them & Leave Them – to protect people and wildlife. This One Health campaign will be primarily implemented by public health communicators who work with government officials and/or local communities. The campaign’s six key messages emphasize the inter-linkages between wildlife and human well-being for pandemic prevention and encourage the campaign target audiences to appreciate (love) wildlife while refraining from touching wildlife or occupying places that wildlife inhabit or feed (leave them … alone). We provide guidance for tailoring the global campaign vision to local ecological and socio-cultural contexts. The campaign is responsive to a recent call by multilateral bodies for governments to prevent pandemics at the source.